Can online political targeting be rendered transparent? Prospects for campaign oversight using the Facebook Ad Library - Somya Mehta; Kristofer Erickson (Internet Policy Review, 2022)
A recent policy development has been voluntary self-regulation of internet platforms through the establishment of online ad archives. Since 2018, concern over the potential misuse of platforms has led to calls for reform of online campaign monitoring. In response, Google, Facebook and Twitter made available repositories of political advertisements appearing on their respective platforms. The intended promise was to make the process of political advertising less of a 'black box' and render voter targeting more transparent to public review. In this paper, we consider whether the Facebook Ad Library actually improves the capability of regulators and the public to oversee online campaigns. Specifically, we analyse a corpus of ads focusing on Brexit in the lead-up to the European Parliamentary Elections in 2019, to determine whether these data are meaningful compared to reporting of offline campaign activity already required under UK Electoral Commission rules. We examine some 234 individual ad campaigns run during a 14-day period leading up to the election using data collection tools available via the Ad Library interface. A content analysis of individual ads combined with data obtained from the archive about the ad sponsor and demographic reach suggests at a coarse level of detail that micro-targeting has taken place. However, limitations of the Ad Library prevent its effectiveness as an oversight mechanism, as reporting obscures details about overall spend, reach and targeting behaviour, key issues for online political advertising. Based on these findings and the methodological challenge of interrogating the Facebook Ad Library, we reflect on the policy effectiveness of supposedly transparent ad archives as a policy tool.
Keywords: 300; Campaigns; Internet oversight; Transparency; Advertising; Politicaltechnology; Political micro-targeting; Online platforms